2016
DOI: 10.1017/s0261444816000306
|View full text |Cite
|
Sign up to set email alerts
|

Research into practice: Listening strategies in an instructed classroom setting

Abstract: This paper considers research and practice relating to listening in instructed classroom settings, limiting itself to what might be called unidirectional listening (Macaro, Graham & Vanderplank 2007) – in other words, where learners listen to a recording, a TV or radio clip or lecture, but where there is no communication back to the speaker(s). A review of the literature relating to such listening reveals a tendency for papers to highlight two features in their introductory lines: first, the acknowledged i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 36 publications
(55 reference statements)
5
68
0
4
Order By: Relevance
“…Listening strategies can be described as listeners' intended plans and mental operations to handle and comprehend incoming speech, such as elaborating or making inferences (Field, 2010;Lau, 2017). Different researchers studying listening in learning a second language have highlighted the importance of strategy use for successful listening, showing that good and poor listeners differ in the frequency and the quality of their strategy use (e.g., Berne, 2004;Graham, 2017). However, research investigating the influence of listening strategy use on listening skills in the Lsch, is barely available.…”
Section: Identifying Student-level Correlates Of Listening Skillsmentioning
confidence: 99%
“…Listening strategies can be described as listeners' intended plans and mental operations to handle and comprehend incoming speech, such as elaborating or making inferences (Field, 2010;Lau, 2017). Different researchers studying listening in learning a second language have highlighted the importance of strategy use for successful listening, showing that good and poor listeners differ in the frequency and the quality of their strategy use (e.g., Berne, 2004;Graham, 2017). However, research investigating the influence of listening strategy use on listening skills in the Lsch, is barely available.…”
Section: Identifying Student-level Correlates Of Listening Skillsmentioning
confidence: 99%
“…Adapting to accented English involves phonological perception, and learners need instruction to acquire phonological perception (Qian, Chukharev-Hudilainen, & Levis, 2018). However, classroom instruction of listening is highly associated with testing rather than teaching of listening, so listening needs to be taught (Graham, 2017). Hence, effective perceptual training for non-native listeners will help them in their accented English listening.…”
Section: Accented English In Communicationmentioning
confidence: 99%
“…Ur (2017) provides examples of evidence-based approaches to teaching vocabulary, some of which are applicable not only to materials writers but also to teachers, such as not teaching lexical sets, and using the L1 for quick translation when teaching vocabulary rather than insisting on explaining in English or guessing from context. Research has shown us the importance of teaching learners how to listen, rather than just testing them on what they have listened to, and we know that although teachers agree that this is important, they do not actually do this in their classrooms (Graham 2017). We know that it is important to allow learners to plan before they carry out a task (and teachers often do that), and that it is important to allow learners to repeat a task (and teachers very rarely do that) (Goh 2017).…”
Section: What Can Research Contribute To Language Teaching?mentioning
confidence: 99%